Tata Kelola Informasi Peta Zona Nilai Tanah pada Kantor Pertanahan Kota Semarang - Niken Susanawati; Retno Sunu Astuti; Budi Puspo Priyadi; Teuku Afrizal (PERSPEKTIF, 2021)
The community doesn’t know the benefits and access to information on land value zone maps at the Semarang City Land Office yet, so the sale and purchase transactions that occur still use the Tax Object Selling Value (NJOP) whose value is below the land market price. The information on the prevailing land value zone map is also assessed that there are not in accordance with market prices, thus making the public file a complaint at the Semarang City Land Office. However, the lack of transparency provided made the community less aware of how the complaint procedure was, and the community was not even involved in determining the price on the applicable land value zone map. The purpose of this study was to determine how the management of land value zone map information at the Semarang City Land Office, which is considered to have not been done optimally. The theory used in this study refers to Vane Klasen's public participation and the transparency (policy, easy access, check and balance principle) proposed by Sedarmayanti. This study uses a qualitative approach and the researcher as a key instrument. The results show that the management of land value zone map information at the Semarang City Land Office has not been maximally implemented, that there is still a need to improve the socialization of benefits and the process of complaints about land value zone map information and public participation.